PENGUATAN TOLERANSI AGAMA “ANALISIS KOMUNIKASI PEMBANGUNAN AGAMA” (Studi Pemerintahan Kota Bogor) - Hasan Sazali (Profetik: Jurnal Komunikasi, 2015)
This article aims at analyzing the empowerment of religious tolerance associated in communicated the regulation of religion conducted by the regional heads and stakeholders of Bogor city goverment in the communication development of religion as well as to identify factors that influence the mayor of bogor city and stakeholders in strengthening religious tolerance in communication religious development.To get the results of a comprehensive analysis in uncovering the role of the actors involved strengthening religious tolerance, this article uses some microsociological theories such as systems theory, symbolic interactionalism theory, and interpenetration theory. It also uses qualitative methods by using a descriptive analytical approach.